Validation of the Culturally Responsive Teaching Survey - Christy M Rhodes (Adult Education Research Conference, 2016)
This investigation examined the psychometric properties of the Culturally Responsive Teaching Survey (CRTS), a newly-developed assessment that measures the cultural responsiveness of adult English language educators’ teaching practices. Findings from two studies revealed a uni-dimensional scale of appropriate internal consistency which yielded positive correlations with multi-cultural knowledge and teaching skills.
Keywords: ESOL; teaching praxis; measurement